Riscos ergonômicos e o trabalho de enfermagem: uma revisão de literatura - Paloma Silva Solano Ramos dos Santos; Alda Aparecida Ferreira dos Santos; Thayssa Souza de Almeida; Bruna Campos Costa; Clara de Oliveira Rennó; Joanir Pereira Passos (Universidade Federal do Estado do Rio de Janeiro, 2012)
a